2016
DOI: 10.4018/ijmmme.2016040101
|View full text |Cite
|
Sign up to set email alerts
|

Automotive Water Cooling System Analysis Subject to Time Dependence and Failure Issues

Abstract: In an automobile engine, the heat transfer cannot be possible without cooling system support. The cooling system has a great importance in the engines. It coolants overheat of the engine, and prevents it from breakdown, that's why a highly reliable cooling system is the necessity of every engine but there are many failure issues with a cooling system which are time dependent. This paper investigates the performance of a water cooling system with the consideration of their significant components by taking the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The author concluded that the brazing process is well-controlled in all production units and for different radiator technologies. Goyal et al [21] researched the reliability measures such as the availability, reliability, and MTTF of the automotive water cooling system considering the time and its failure rate parameters using Markov process and supplementary variable technique. Also, they investigated the sensitivity of these reliability characteristics to enhance the functioning of the water cooling system.…”
Section: Figure 2 Technical Drawing Geometrymentioning
confidence: 99%
“…The author concluded that the brazing process is well-controlled in all production units and for different radiator technologies. Goyal et al [21] researched the reliability measures such as the availability, reliability, and MTTF of the automotive water cooling system considering the time and its failure rate parameters using Markov process and supplementary variable technique. Also, they investigated the sensitivity of these reliability characteristics to enhance the functioning of the water cooling system.…”
Section: Figure 2 Technical Drawing Geometrymentioning
confidence: 99%